Pengaruh Model Pembelajaran Problem Based Learning (PBL) Terhadap Kemampuan Berpikir Kritis dan Hasil Belajar Peserta Didik Pada Mata Pelajaran Kearsipan Kelas X OTKP Di SMK Negeri 1 Sooko Mojokerto - Elsa Putri Pebriyani; Triesninda Pahlevi (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
The purpose of this research to determine that the effect of the Problem Based Learning (PBL) learning model on critical thinking skills of class X SMKN 1 Sooko Mojokerto, to determine that the effect of Problem Based Learning (PBL) learning model on learning outcomes of class X SMKN 1 Sooko Mojokerto, to determine the implementing of Problem Based Learning (PBL) learning model to the basic competence in implementing maintance procedures archive at SMKN 1 Sooko Mojokerto in academic year 2019/2020. This the research design that used was quasi experimental with method non-equivalent control group design. The research were all students of class X OTKP 2 and X OTP 3 and class X OTKP 3 as the control class and X OTKP 2 as the experimental class. The instrument that used was a critical thinking skill test and multiples choice test to measure student learning outcomes and the technique pf anlizing, data used homogeneity test, normality test, gain score analysis, and t test (hypotesis). The result indicate that the Problem Based Learning (PBL) learning model had a significant effect on critical thinking skills as evidence by the acquisition of t-test with a significant level of 0.000 (0,00) < 0,05. The result also showed that the Problem Based Learning (PBL) learning model has a significant effect on student learning outcome as evidence by the acquisition with a significance level of 0.000 (0,00) < 0,05. In addition, the experimental class has an average of critical thinking skilss higher than the control class with the conventional learning model with an average of 83 experimental classes and 72 control classes. On the average of posttest learning outcome the experimental class has an average higher than control with an experimental average of 85,29 and control class of 74,85. So it was concluded that Problem Based Learning (PBL) learning model had an influence the crtical thinking skill an learning outcomes of students of class X OTKP SMKN 1 Sooko Mojokerto.